2012
DOI: 10.1002/adsc.201200067
|View full text |Cite
|
Sign up to set email alerts
|

Regio‐ and Stereoselective Hydroxylation of Optically Active α‐Ionone Enantiomers by Engineered Cytochrome P450 BM3 Mutants

Abstract: Abstract:The selective hydroxylation of an unactivated C À H bond is a crucial step in the synthesis of fine chemicals such as hydroxylated terpenoids. In the present study, the ability of 40 cytochrome P450 BM3 mutants to perform the regio-and stereoselective hydroxylation of a-ionone has been investigated. Based on their activity and selectivity to produce 3-hydroxy-a-ionone from racemic a-ionone, 6 BM3 mutants were selected. Out of these, 3 mutants (M01 A82W, M11 A82W and M11 V87I) showed high selectivity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 69 publications
3
45
0
Order By: Relevance
“…22,25 In order to rationalize the observed ring preference for hydroxylation, in silico docking studies were performed with BM3 mutant M11 and 2 as a model, using the GOLD (version 5.2) software 35 and the docking settings as previously described. 36 Docking of 2 into M11 predominantly shows the occurrence of binding poses in which 2 is docked with its dimethyl phenyl ring toward the heme group, with either 3'-methyl or C-4' in closest proximity of the heme iron center (see Figure 5, panels A and B, respectively). These binding orientations are stabilized by formation of a hydrogen bond between the 2 carboxyl group and the side-chain hydroxyl group of Ser72.…”
Section: Aromatic Ring Preference For Hydroxylation By P450 Bm3 Mutantsmentioning
confidence: 98%
“…22,25 In order to rationalize the observed ring preference for hydroxylation, in silico docking studies were performed with BM3 mutant M11 and 2 as a model, using the GOLD (version 5.2) software 35 and the docking settings as previously described. 36 Docking of 2 into M11 predominantly shows the occurrence of binding poses in which 2 is docked with its dimethyl phenyl ring toward the heme group, with either 3'-methyl or C-4' in closest proximity of the heme iron center (see Figure 5, panels A and B, respectively). These binding orientations are stabilized by formation of a hydrogen bond between the 2 carboxyl group and the side-chain hydroxyl group of Ser72.…”
Section: Aromatic Ring Preference For Hydroxylation By P450 Bm3 Mutantsmentioning
confidence: 98%
“…Also within our own lab, isolated CYP BM3 mutants have previously been successfully applied for biosynthesis of drug metabolites on a preparative scale [32][33][34][35][36]39,47,48]. During our in vitro experiment, bioconversion was monitored in time (see Fig.…”
Section: In Vitro Biotransformation Of Netmentioning
confidence: 99%
“…To overcome this limitation, various protein engineering strategies have been successfully applied to generate CYP BM3 mutants that can be used for the production of both human relevant and CYP BM3 unique metabolites [2,3,26]. Over the years, a diverse library of CYP BM3 mutants has been constructed within our group by a combination of random and site-directed mutagenesis [27][28][29][30][31][32][33][34]. It has been shown that these mutants metabolize a wide range of substrates, including marketed drugs [28,30,35,36] and steroids [29,32,34], with varying catalytic activities and regio-and stereoselectivities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various drug metabolizing mutants of cytochrome CYP102A1 from Bacillus megaterium (CYP BM3) have been described, and from the onset, computational tools were integrated in the rationalization and design of novel mutants [49,71,72]. Two mutants of CYPBM3 were experimentally shown to catalyze the stereospecific hydroxylation of α-ionones [73]. By using efficient free energy calculations, the relative binding free energies of the substrates and the products could be determined in both mutants (see Figure 10.5).…”
Section: Effect Of Mutationsmentioning
confidence: 99%